An Unusual Extreme Rainfall Event in Canberra Australia on February 2018. Issue 8 (29th April 2019) - Deng, Difei; Ritchie, Elizabeth A.
Abstract: A case of an extreme rainfall event in Canberra, the capital city of Australia, on 24–25 February 2018 is investigated. Canberra received more than the long‐term statistical February total rainfall within 6 hr on that day, causing overwhelming flash flooding in the city. In contrast to many coastal cities or tropical regions, Canberra is located at the boundary between the tropics and extratropics and is usually dry and warm in February. The diagnostic analysis shows that this relatively rare brief heavy rainfall was the joint effects of lower‐level warm, moist conveyor belts, the remnants of tropical cyclone Kelvin, surface cold fronts, and a midlatitude trough at middle to upper levels. The lower‐level northeast and west conveyor belts of water vapor contributed to the accumulation of moisture and created favorable conditional instability over Canberra by transporting tropical moist and warm air from Coral Sea and from the Kelvin remnant to Canberra prior to and during the rainfall period. Enhanced uplift was triggered by the arrival of a cold front in the warm, moist unstable air. The rainfall reached a peak 13.6 mm in 30 min soon after a low‐level frontal updraft coupled with middle‐ to upper‐level dynamical uplift ahead of the midlatitude trough. After the passage of the upper‐level trough, the dry, cold air in the rear of the trough stabilized and dried the atmosphere above Canberra. The rainfall decreased and ended rapidly. Key Points: Extreme rain events are not limited to coastal regions but, in some circumstances, can also occur in inland areas that are normally dry In a recent rare extreme rainfall event, Canberra received more than the long‐term statistical February total rainfall within 6 hr It was the joint effects of lower‐level warm, moist conveyor belts, the TC remnant, cold fronts, and midlatitude trough